Distribution Analysis of Nitrate and Phosphate in Coastal Area: Evidence from Pangkep River, South Sulawesi - Waode Rustiah; Alfian Noor; Maming Maming; Muhammad Lukman; Baharuddin Baharuddin; Andi Tenri Fitriyah (Hasanuddin University, 2019)
Nitrate and phosphate nutrient and the other oceanographical parameter are part of an indicator to evaluate the quality of the water environment. Our research aims to determine the nitrate and phosphate levels in the water and sediment along the Pangkep coastal area. The research was conducted in February 2018 in coastal Pangkep using five sampling stations. Physico-chemical parameters of the water, such as temperature, pH, salinity, and dissolved oxygen were measured directly, whereas nitrate and phosphate parameters were analyzed using a spectrophotometer. In addition, nitrate and phosphate parameters from the sediment were measured using an atomic absorption spectrophotometer. The sediment nitrate values ranged from 0.026-0.442 mg/L, and the water nitrate values ranged from 0.018-0.063 mg/L. Moreover, the phosphate values from sediment ranged from 0.019-0.306 mg/L, and the phosphate values from the water ranged from 0.13-0.056 mg/L. The results show decreasing values of nitrate and phosphate concentration in the water and sediment starting from the estuary to the sea. The highest values were indicated in the estuary, which represents a eutrophic condition in the environment. Nutrient enrichment in coral reefs occurs and mixes with oceanographic conditions resulting in oxygen depletion and changes in benthic community structure.